Maternal outcomes and birth interventions among women who begin labour intending to give birth at home compared to women of low obstetrical risk who intend to give birth in hospital: A systematic review and meta-analyses. (April 2020) - Reitsma, Angela; Simioni, Julia; Brunton, Ginny; Kaufman, Karyn; Hutton, Eileen K
Abstract: Background: We previously concluded that risk of stillbirth, neonatal mortality or morbidity is not different whether birth is intended at home or hospital. Here, we compare the occurrence of birth interventions and maternal outcomes among low-risk women who begin labour intending to birth at home compared to women intending to birth in hospital. Methods: We used our registered protocol (PROSPERO, http://www.crd.york.ac.uk, No.CRD42013004046) and searched five databases from 1990–2018. Using R, we obtained pooled estimates of effect (accounting for study design, study setting and parity). Findings: 16 studies provided data from 500, 000 intended home births for the meta-analyses. There were no reported maternal deaths. When controlling for parity in well-integrated settings we found women intending to give birth at home compared to hospital were less likely to experience: caesarean section OR 0.58(0.44, 0.77); operative vaginal birth OR 0.42(0.23, 0.76); epidural analgesia OR 0.30(0.24, 0.38); episiotomy OR 0.45(0.28, 0.73); 3rd or 4th degree tear OR 0.57(0.43, 0.75); oxytocin augmentation OR 0.37(0.26, 0.51) and maternal infection OR 0.23(0.15, 0.35). Pooled results for postpartum haemorrhage showed women intending home births were either less likely or did not differ from those intending hospital birth [OR 0.66(0.54, 0.80) and RR 1.30(0.79, 2.13) from 2 studies that could not be pooled with the others]. Similar results were found when data were stratified by parity and by degree of integration into health systems. Interpretation: Among low-risk women, those intending to birth at home experienced fewer birth interventions and untoward maternal outcomes. These findings along with earlier work reporting neonatal outcomes inform families, health care providers and policy makers around the safety of intended home births. Funding: Partial funding: Association of Ontario Midwives open peer reviewed grant.